Violence and crime in the family patterns, causes, and consequences - Maxwell, Sheila Royo; Blair, Sampson Lee (Emerald, 2015)
In virtually all societies, crime is an ever-present problem. Although families are often envisioned as a 'safe haven', criminologists and family researchers have found the familial context to be at the core of many forms of crime and violence. Family members often find themselves as victims of crime and violence, often perpetrated by yet another family member. The unique nature of family relationships, such as those between children and parents, sometimes lead to intergenerational patterns of violence within families. Understandably, societies often struggle to address crime and violence within families; as such behaviors are often unreported and even concealed. Even beyond the family, crime and criminal behavior can often directly impact familial relationships, such as with the incarceration of a spouse or parent. This multidisciplinary volume of CPFR will address topics such as: child abuse and neglect, spousal violence, incarceration and parenting, community crime and family well-being, family life and delinquency, intrafamily violence, and policy-related issues pertaining to family violence.
Keywords: Social Science -- Criminology.; Sociology: family & relationships.; Family violence.; elektronické knihy; electronic books